College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter R - Section R.7 - Rational Expressions - R.7 Assess Your Understanding - Page 71: 61


LCM =$x(x-1)^{2}(x+1)(x^{2}+x+1)$

Work Step by Step

Step 1: Factor each polynomial completely. $x^{3}-x=x(x^{2}-1)=$ ... recognize a difference of squares $=x(x-1)(x+1)$ $x^{3}-2x^{2}+x=x(x^{2}-2x+1)$ ... recognize perfect square $=x(x-1)^{2}$ $ x^{3}-1=\qquad$... a difference of cubes, $=(x-1)(x^{2}+x+1)$ Step 2: The LCM is the product of each of these factors raised to a power equal to the greatest number of times that the factor occurs in the polynomials. LCM =$x(x-1)^{2}(x+1)(x^{2}+x+1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.